Reindeer Pasture Biomass Assessment Using Satellite Remote Sensing - Colpaert, Alfred; Kumpula, Jouko; Nieminen, Mauri (ARCTIC, 2003)
The present state of reindeer winter and summer pastures in northern Finland has been mapped using field sampling, remote sensing, and GIS. The winter pasture inventory was made during 1995-96 and the summer pasture inventory during 1997-98. Winter pastures can be divided into ground lichen and arboreal lichen pastures. Autumn pastures, including pastures with grasses, dwarf shrubs, and mushrooms, were also mapped and added to the inventory of winter pastures. Summer and winter pastures partly overlap, but the main pasture areas are clearly distinct from each other. Major summer feeding areas are marshes, mires and river meadows, and mountain birch woodland. Biomass data were obtained by volumetric calculations of lichens and standard samples of the green parts of summer fodder plants. The results show that the most abundant lichen resources are found in the northern part of the management area, while the most abundant summer pasture resources prevail in the middle and southern parts. The overall accuracy of the winter pasture mosaic is 88%, with a Kappa coefficient of 0.84. The overall accuracy of the summer pasture mosaic is 84%, with a Kappa coefficient of 0.81. On a cartographié l'état actuel des pâturages d'hiver et des estives du renne dans le nord de la Finlande à l'aide de l'échantillonnage sur le terrain, de la télédétection et du SIG. L'inventaire des pâturages d'hiver a été réalisé au cours de 1995-1996 et celui des estives au cours de 1997-1998. Les premiers peuvent être divisés en pâturages à lichens terricoles et en pâturages à lichens corticoles. Les pâturages d'automne, incluant ceux comprenant des herbages graminés, des arbustes nains et des champignons, ont également été cartographiés et ajoutés à l'inventaire des pâturages d'hiver. Ces derniers et les estives se chevauchent en partie, mais leurs zones principales sont nettement séparées. Les zones majeures de broutage utilisées en été sont les marais, les bourbiers et les prairies riveraines, ainsi que la forêt-parc de bouleau fontinal. Les ...